Photocatalytic degradation of basic red dye utilizing sol-gel derived TIO2 supported on montmorillonite: characterization, process and kinetic studies - Muhammed Ahshath A. Jamal Muhammed (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
The present study deals with the investigation of photocatalytic degradation of Basic Red 46 dye (BR46) under ultraviolet ray using TiO2 supported onto montmorillonite as photocatalyst. tiO2 was pepared by sol-gel method and the sol obtained was used for haterocoagulation of na-montmorillonite. The TiO2 photocatalyst was characterized by using Sanning Elelctron Microscopy (SEM). The determination of photocatalytic activity was observed as a function of initial dye concentration, pH of the dye solution and TiO2 photocatalyst dosage. Langmuir -Hinshelwood kinetic model was applied to experimental data and apparent reaction rate contants values were calculated.